2010
DOI: 10.1590/s1516-44462010000100006
|View full text |Cite
|
Sign up to set email alerts
|

Adding motivational interviewing and thought mapping to cognitive-behavioral group therapy: results from a randomized clinical trial

Abstract: Objective: Recent factor-analytic studies of obsessive-compulsive disorder identified consistent symptom dimensions. This study was designed in order to observe which obsessive compulsive symptom dimensions could be changed by adding two individual sessions of motivational interviewing and thought mapping of cognitive-behavioral group therapy using a randomized clinical trial. Method: Forty outpatients with a primary diagnosis of obsessive-compulsive disorder were randomly assigned to receive cognitive-behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…A recent study demonstrated that cognitive behavioral group therapy was more effective if preceded by two individual sessions of motivational interviewing and thought mapping. The symptom reduction was still maintained at a 3-months follow up (48). …”
Section: Discussionmentioning
confidence: 93%
“…A recent study demonstrated that cognitive behavioral group therapy was more effective if preceded by two individual sessions of motivational interviewing and thought mapping. The symptom reduction was still maintained at a 3-months follow up (48). …”
Section: Discussionmentioning
confidence: 93%
“…Some variations of CBT have been also developed, including CBT with bibliotherapy [29], CBT with cognitive rehabilitation [30] CBT with motivational interviewing [31], CBT with internet supported group [32] and isolated bibliotherapy [33][34][35]. In conclusion, these studies reveal that there are a percentage of hoarders who do not benefit the current CBT approaches.…”
Section: Methods Based On Cbtmentioning
confidence: 99%
“…Upon making a diagnosis, the clinician must determine whether the patient's insight is good or fair; poor; or is absent/has delusional beliefs. [11,12] However, insight is a multidimensional concept, including both the recognition that the cause of the belief is psychological/psychiatric and the willingness to consider that the belief may be false.…”
Section: Clinical Significance Of New Insight Specifiersmentioning
confidence: 99%